The names of States in International Relations: officiality, formality, and patterns of composition - Gallego Cosme, Mario (Scientific journal of social studies, 2024)
This paper offers a general review of the names of States as a subject of study of great interest for fields of knowledge in which this issue is relevant, as in International Relations and diplomacy. It is a subject with various facets and that presents complexities that are not always evident, which, consequently, justifies their study and analysis, not only from an academic perspective, but also because they are useful in practical terms. From an exploratory perspective, the fundamental aspects of this object of study, located at the crossroads between geography, political science and linguistics, are taken into account. For this purpose, its main concepts of this matter are reviewed —particularly those of officiality and formality— and a categorization of the formal names of the States is proposed based on the elements that compose them. It is hoped that this contribution, raised from the point of view of the Spanish language, will create new bases for future developments in this field of study that, by necessity, must be multidisciplinary.